Distinguishing Characteristics of COVID-19-Associated Mucormycosis; a Case Series - Seyedhadi Samimiardestani; Shirin Irani; Mehrdad Hasibi; Maral Seyedahadi; Shahin Bastaninejad; Mohammadreza Firouzifar; Mojataba Mohammadi Ardehali; Sina Berijani; Reza Erfanian; Mohammad Ali Kazemi; Afshar Etemadi-Aleagha; Abolfazl Rahimi; et al. (Archives of Academic Emergency Medicine, 2022)
Introduction: Since the emergence of COVID-19 pandemic, several articles have reported the co-existence of mucormycosis and COVID-19. This study aimed to distinguish the characteristics of COVID-19-associated rhinocerebral mucormycosis.